2015
DOI: 10.1111/jsm.13028
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Components of Pelvic Floor Muscle Tone in Women with Provoked Vestibulodynia: A Perspective Based on a Review of the Literature

Abstract: Aim Pelvic floor muscle (PFM) dysfunctions, especially elevated tone or tension, are suggested to play an important role in the pathophysiology of provoked vestibulodynia (PVD). However, the involvement of the PFMs remains misunderstood as the assessment of muscle tone is complex and requires a thorough understanding of muscle physiology in relation to the characteristics and limitations of current PFM assessment tools. The aim of this review was to describe the structures and mechanisms invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Stiffness, RFD, and relative peak force were all higher at the faster speed of opening compared to the slower speed. While, to our knowledge, this is the first study to demonstrate the velocity dependent nature of passive PFM forces in vivo, the results are in line with other research in skeletal muscle function and modeling . The stress relaxation response in tissues has been shown to be dependent on strain rate and hold time .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Stiffness, RFD, and relative peak force were all higher at the faster speed of opening compared to the slower speed. While, to our knowledge, this is the first study to demonstrate the velocity dependent nature of passive PFM forces in vivo, the results are in line with other research in skeletal muscle function and modeling . The stress relaxation response in tissues has been shown to be dependent on strain rate and hold time .…”
Section: Discussionsupporting
confidence: 85%
“…Specifically, we found that absolute peak force, relative peak force, and stiffness during passive tissue elongation were systematically higher in the first trial compared to subsequent trials at both velocities. Morin et al reported that passive forces were significantly higher in the first two cycles compared to the subsequent three cycles, and later attributed this finding to thixotropy . Thixotropy is a property of skeletal muscle that refers to an initially higher resistance to passive lengthening of the muscle which is caused by covalent bonds formed between actin and myosin monofilaments After the initial phases of a first stretch, thixotropy should no longer be present .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transperineal three-dimensional real-time ultrasound imaging has been used to investigate the morphology and function of the PFM in PVD patients 77, 78 . Because this method does not involve vaginal penetration (as with intravaginal palpation and EMG assessment) and is therefore pain-free, it has the advantage of limiting bias caused by the participant’s pain and anxiety during the procedure 79 . In accordance with previous studies, ultrasound imaging showed higher PFM tone and lesser contractile capacities among PVD patients 7779 .…”
Section: Pelvic Floor Muscle Dysfunctionmentioning
confidence: 99%
“…Because this method does not involve vaginal penetration (as with intravaginal palpation and EMG assessment) and is therefore pain-free, it has the advantage of limiting bias caused by the participant’s pain and anxiety during the procedure 79 . In accordance with previous studies, ultrasound imaging showed higher PFM tone and lesser contractile capacities among PVD patients 7779 . These findings suggest that PVD patients display PFM impairments which are not limited to a defense reaction but are rather chronic 78 .…”
Section: Pelvic Floor Muscle Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation